Seismic Hazard Analysis of Putrajaya Area Using PSHA Method - MASTOR, AMIR RAZIQ (Universiti Teknologi PETRONAS, 2020)
This study constructs”probabilistic seismic hazard analysis (PSHA) maps for Putrajaya that are based on the distribution and long-term recurrence behaviour of the spatial distribution of earthquake observed in historic time.